Reusability Of Zinc Oxide Nanorod For Photocatalytic Decomposition Of Rhodamine B Dye After Copper Metal Deposition - Le, Anh Thi (2018)
Advanced oxidation process based on semiconductor photocatalysts is an emerging technique for wastewater treatment. However, the lifetime of these semiconductor photocatalysts is yet to be fully studied. After heavy metal removal, most active sites of catalyst are blocked by heavy metal. Therefore, it affects the subsequent photocatalytic performance differently in organic dye removal. In this work, ZnO nanorods (NRs) and nanodisks (NDs) were synthesized by precipitation method and evaluate the photocatalytic activity to degrade Rhodamine B dye after heavy metal deposition. The average length and diameter of ZnO NRs were 497.34 ± 15.55 nm and 75.78 ± 10.39 nm, respectively. The ZnO NDs have average diameter of 2.12 ± 0.39 µm and thickness of 74.91 ± 17.67 nm. The photodegradation of RhB dye by ZnO particles followed first-order kinetic reaction. ZnO NRs removed effectively heavy metal ions such as Cu(II), Ag(I) and Pb(II) ions with efficiency of 100%, 97.92% and 85.18%, respectively under exposure of UV light for 1 hour. However, poor removal efficiency, i.e. 14.83%, 8.62%, 7.23% and 4.76%, respectively was observed for Cr(VI), Mn(II), Cd(II) and Ni(II). These heavy metal ions were removed in the forms of metals or metal oxide via reduction/oxidation or adsorption mechanisms. The degradation efficiencies of RhB dye by Cu/ZnO, Ag/ZnO, Mn/ZnO, Cd/ZnO and Ni/ZnO hybrid particles were better than ZnO particles but not the case of Pb/ZnO and Cr/ZnO hybrid particles. In conclusion, the ZnO NRs in general showed a remarkable ability to degrade RhB dye under UV irradiation after heavy metal deposition.